2021
DOI: 10.3390/en14175574
|View full text |Cite
|
Sign up to set email alerts
|

GHG and NH3 Emissions vs. Energy Efficiency of Maize Production Technology: Evidence from Polish Farms; a Further Study

Abstract: The paper determines the effect of selected cultivation technologies, including production chain energy inputs (growing, harvest, heap forming) on greenhouse gas emissions (GHGs) to the atmosphere. The data for the study was collected from 13 actually operating family farms ranging in size from 2 to 13 ha, located in the Podlaskie voivodship (Poland). GHG and ammonia (NH3) emissions from natural and mineral fertilisation as well as GHGs from energy carriers in a form of fuels (ON) were estimated. The average G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The attainable temperature in the firebed can reach up to 900 • C. Importantly, the flame in the combustion process should be dark yellow in colour, as this allows the temperature to be controlled and limits slagging. During combustion, straw briquette fuel emits an inconsiderable amount of greenhouse gases and CO 2 [39], unlike traditional coal, where particulate matter can fall within 20-30 metres from the firebed.…”
Section: Discussionmentioning
confidence: 99%
“…The attainable temperature in the firebed can reach up to 900 • C. Importantly, the flame in the combustion process should be dark yellow in colour, as this allows the temperature to be controlled and limits slagging. During combustion, straw briquette fuel emits an inconsiderable amount of greenhouse gases and CO 2 [39], unlike traditional coal, where particulate matter can fall within 20-30 metres from the firebed.…”
Section: Discussionmentioning
confidence: 99%
“…Dang et al, (2017) reported that the lag period for methane production was significantly reduced in reactors with granular activated carbon (GAC) and the cumulative methane production was 18 times higher than that of the control [ 71 ]. Konieczna et al, (2021) studied the relationship between energy efficiency and greenhouse gas (GHG) emissions to the atmosphere from the silage maize plantation technologies [ 72 ]. They reported that the higher the energy efficiency of silage maize plantations, the lower the air pollution emissions in the form of GHG.…”
Section: Discussionmentioning
confidence: 99%
“…(2) in spare parts and materials used for repairs; (3) in a direct energy carrier (fuel and Energies 2021, 14, 8584 6 of 15 electrical energy); (4) in consumables and raw materials; as well as in human labor [9,10,20]. Energy intensities accumulated for the practices undergoing study have been calculated from the following formula:…”
Section: Cumulative Energy Intensity Calculationmentioning
confidence: 99%
“…However, in animal production, adequate natural fertilizer management, through the use of the fertilizer for biogas and energy production, is one of the ways of ensuring sustainable production [8]. Increasing agricultural production in the European Union countries comes with the growing energy and fuel demands of agricultural machinery and tractors, which result in an increase in CO 2 emissions [1, 9,10]. According to Wójcicki [11], converted into energy units, the value of the final agricultural production in Poland was 900 m GJ of cumulative energy, or 435 m GJ when the energy value was considered.…”
Section: Introductionmentioning
confidence: 99%